Challenges in Anesthetic Care for Chest Wall Reconstruction in a Child with Sternal Agenesis: A Case Report - Arthur R. Fernandes; Victor T. Guilarducci; Luiz F. A. P. de Oliveira; Marina A. Delgado (Bali Journal of Anesthesiology)
Congenital absence of the sternum is a rare chest wall malformation associated with a decrease in the chest wall compliance and respiratory failure. This study describes the case of a 6-month-old patient diagnosed with agenesis of the sternum, hypoplasia of the costal arches, dextrocardia, atrial septal defect, and hepatomegaly. Shortly after birth, the patient developed respiratory failure and paradoxical breathing, requiring mechanical ventilation with unsuccessful attempts at weaning. Following a multidisciplinary discussion, she underwent surgery for chest wall reconstruction. This case report highlights the challenges of perioperative anesthetic management and underscores the importance of hemodynamic and ventilatory management.